2009
DOI: 10.1182/blood.v114.22.903.903
|View full text |Cite
|
Sign up to set email alerts
|

Cytochrome b5 Reductase T116S Mutation and Hemolysis in Sickle Cell Disease.

Abstract: 903 Abstract Background: Deficiency of NADH-cytochrome b5 reductase (cytb5r, EC 1.6.2.2) is responsible for congenital methemoglobinemia. This enzyme exists in soluble and membrane-bound forms. The soluble erythrocytic cytb5r isoenzyme is involved in cytochrome b5 reduction and in erythrocyte methemoglobin reduction; the membrane-bound microsomal enzyme participates in a fatty acid desaturation complex and in drug metabolism. The cytb5r isoform… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…On this basis, NEDD4L might be implicated directly in SCD-related PH pathogenesis and a target for further prognostic and therapeutic application [43]. Nouraie et al,(2009), investigated CYBR5 T116S polymorphism and suggested a protective effect against PH. CYBR5 T116S polymorphism was associated with lower TRVs, possibly attributed to lower hemolysis levels in the carriers of this SNP [45].CYBR5 T116S is a frequently identified polymorphism in African children and may be associated with protection from severe malariarelated anemia.…”
Section: Role Of Gene Polymorphisms In Pathogenesis and Prognosis Of ...mentioning
confidence: 99%
See 1 more Smart Citation
“…On this basis, NEDD4L might be implicated directly in SCD-related PH pathogenesis and a target for further prognostic and therapeutic application [43]. Nouraie et al,(2009), investigated CYBR5 T116S polymorphism and suggested a protective effect against PH. CYBR5 T116S polymorphism was associated with lower TRVs, possibly attributed to lower hemolysis levels in the carriers of this SNP [45].CYBR5 T116S is a frequently identified polymorphism in African children and may be associated with protection from severe malariarelated anemia.…”
Section: Role Of Gene Polymorphisms In Pathogenesis and Prognosis Of ...mentioning
confidence: 99%
“…Nouraie et al,(2009), investigated CYBR5 T116S polymorphism and suggested a protective effect against PH. CYBR5 T116S polymorphism was associated with lower TRVs, possibly attributed to lower hemolysis levels in the carriers of this SNP [45].CYBR5 T116S is a frequently identified polymorphism in African children and may be associated with protection from severe malariarelated anemia. This polymorphism may be related to increased cytochrome b5 reductase activity which in turn may explain its protective effect on hemolysis through increased anti-oxidant [46].…”
Section: Role Of Gene Polymorphisms In Pathogenesis and Prognosis Of ...mentioning
confidence: 99%
“…On this basis, NEDD4L may be implicated directly in SCD-related PH pathogenesis and a target for further prognostic and therapeutic application [54]. Nouraie et al (2009) [56] investigated CYBR5 T116S polymorphism and suggested a protective effect against PH. CYBR5 T116S polymorphism was associated with lower TRVs, possibly due to the lower hemolysis levels among carriers of this SNP56.…”
Section: Role Of Gene Polymorphisms In Pathogenesis and Prognosis Of ...mentioning
confidence: 99%